1995
DOI: 10.1152/ajplung.1995.269.5.l574
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inhibits L-arginine uptake by pulmonary artery endothelial cells

Abstract: Under physiological conditions, L-arginine transport by porcine pulmonary artery endothelial cells (PAEC) is mediated by system y+, a sodium-independent transport system that accounts for 60 +/- 5% of L-arginine transport, and system Bo,+, a sodium-dependent system that accounts for 40 +/- 5% of transport. Because NO production is dependent on intracellular L-arginine content and intracellular L-arginine content depends on transport of extracellular L-arginine, we examined the effect of hypoxia on L-arginine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…Hypoxia inhibits L-arginine transport with no significant effect on CAT-1 mRNA expression or membrane protein levels. 23,24 This effect is not reversible after a return to normoxia for 24 hours. 24 There is evidence that the placental bed in preeclampsia is hypoxic, 25 where inflammatory leukocytes in the hypoxic intervillous space may be exposed to damage of membrane CAT proteins that impairs function.…”
Section: Discussionmentioning
confidence: 96%
“…Hypoxia inhibits L-arginine transport with no significant effect on CAT-1 mRNA expression or membrane protein levels. 23,24 This effect is not reversible after a return to normoxia for 24 hours. 24 There is evidence that the placental bed in preeclampsia is hypoxic, 25 where inflammatory leukocytes in the hypoxic intervillous space may be exposed to damage of membrane CAT proteins that impairs function.…”
Section: Discussionmentioning
confidence: 96%
“…The Arg content of endothelial cells is derived primarily from plasma membranedependent transport of extracellular Arg, but can also be synthesized from L-cit [19]. BLOCK et al [20] showed that exposure to hypoxia causes significant reduction in the transport of Arg, only accompanied by a decrease in intracellular Arg content after long-term exposure to hypoxia. SU and BLOCK [21] demonstrated that hypoxia time dependently inhibits the synthesis of Arg from L-cit in pulmonary artery endothelial cells.…”
Section: L-arginine Availabilitymentioning
confidence: 99%
“…From Figures 1 and 2 it can be seen that the control curves fall approximately mid-way between those for 400 mM L-arginine and 10 mM Llysine, suggesting that the concentration of this endogenous Larginine is close to the EC 50 , or around 1 ± 7 mM (see Results and Figure 4). As the intracellular concentration of L-arginine is at least 100 fold greater than this (Gold et al, 1989;Baydoun et al, 1990;Block et al, 1995;Bogle et al, 1996), we can speculate that only a small amount of diusion and/or reverse Figure 7 Isoprenaline concentration-response curves in mesenteric arteries constricted with 50 mM PGF 2a , and in the presence of Larginine (400 mM) or L-arginine plus L-lysine (10 mM). Each point is the mean of 5 ± 7 experiments, and symbols are mean+s.e.mean.…”
Section: Concentration Dependence Of Response To L-argininementioning
confidence: 99%
“…It is generally assumed that under normal physiological conditions L-arginine is in excess, as the EC 50 for activation of eNOS is *1-10 mM (Palmer & Moncada, 1989;Su et al, 1997), yet the intracellular concentration of L-arginine in the endothelial cell is signi®cantly greater than 100 mM (Baydoun et al, 1990;Block et al, 1995), and sucient to maximally activate the enzyme (Su et al, 1997). Most studies on isolated preparations do not therefore include L-arginine in the extracellular medium.…”
Section: Introductionmentioning
confidence: 99%